Superiority of Females Than Males & Neuters w.s.r. To Gems - Dr. Ravneet Kaur Chahal, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Gems are unique and radiant in nature. Everyone especially women are fond of wearing these  gems. These are mostly expensive stones. Therapeutically gems are used to heal certain diseases by oral use and by wearing them as ornaments too. According to Jyotish Shastra to pacify or enhance the planetary effects, gems are usually used only ornamentally. In Ayurveda1 if a person is of Vata Parkriti (air) must wear ruby, garnet and yellow sapphire. Pitta (fire) constitution need to wear pearl, moonstone, amethyst, emerald and blue sapphire. Kapha  (water) constitution should wear ruby, garnet. In Rasa Shastra, for preparing medicines these gems must be of good quality and should be free from Doshas (impurities). If impure gems are used in either ways then the effects must not be satisfactory rather negative. These are categorised as Ratna (gems) and Upratna (subcategory gems) in Rasa Shastra. Ratna are used more usually than Upratna in Parada  (mercury) preparations so subcategorized.In every science exceptions are always there. Heerak (diamond)  is of three types i.e. male, female, neuter. Here diamonds are exceptionally used in case of women. This is subject of controversy that what can be the reason for this usage. Females are more resistant to the bad effects of gems or having more bearable energy than males and neuters.